Differences in grip force control between young and late middle-aged adults - Zheng, Lianrong; Li, Kunyang; Wang, Qian; Chen, Wenhui; Song, Rong; Liu, Guanzheng (Australasian physical & engineering sciences in medicine, 2017)
Grip force control is a crucial function for human to guarantee the quality of life. To examine the effects of age on grip force control, 10 young adults and 11 late middle-aged adults participated in visually guided tracking tasks using different target force levels (25, 50, and 75% of the subject’s maximal grip force). Multiple measures were used to evaluate the tracking performance during force rising phase and force maintenance phase. The measurements include the rise time, fuzzy entropy, mean force percentage, coefficient of variation, and target deviation ratio. The results show that the maximal grip force was significantly lower in the late middle-aged adults than in the young adults. The time of rising phase was systematically longer among late middle-aged adults. The fuzzy entropy is a useful indicator for quantitating the force variability of the grip force signal at higher force levels. These results suggest that the late middle-aged adults applied a compensatory strategy that allow allows for sufficient time to reach the required grip force and reduce the impact of the early and subtle degenerative changes in hand motor function.